2001
DOI: 10.1080/714005002
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management in Irish Healthcare

Abstract: This article reports the findings from a quantitative research study of quality management within the Irish Healthcare Sector. The survey results indicate that quality management has not fully permeated the sector although indications are that interest is growing in adopting this approach. The study revealed that, for all the hospitals, an aim to improve the quality of care delivered was the predominant factor for the uptake of quality. The findings suggest that even though quality management is in its infancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hartline and Ferrell (1996) presented evidence that satisfaction felt by the first-line customer-contact employees is associated with service quality (Ennis & Harrington, 2001). Satisfied employees tend to be more engaged in providing quality services (Hallowell et al, 1996;Yee, Yeung, & Cheng, 2008).…”
Section: Service Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…Hartline and Ferrell (1996) presented evidence that satisfaction felt by the first-line customer-contact employees is associated with service quality (Ennis & Harrington, 2001). Satisfied employees tend to be more engaged in providing quality services (Hallowell et al, 1996;Yee, Yeung, & Cheng, 2008).…”
Section: Service Qualitymentioning
confidence: 97%
“…Health-care organisations have also used a variety of measurement tools, including employee feedback for service quality (Ennis & Harrington, 2001). Yoon, Choi, and Park (2007) suggested that employees as internal customers should be able to assess service quality for better patient outcome, such as short lengths of stay in the hospital, reduced hospital infection, and reduction in medical errors.…”
Section: Service Qualitymentioning
confidence: 99%
“…Indeed the uptake of quality initiatives in Ireland is becoming more popular, and not just solely in the manufacturing sector. Indications are present that there is an increasing commitment to quality initiatives in service sectors such as the health care sector (Ennis and Harrington, 2001). However, although the uptake of quality initiatives by Irish companies is increasing, research indicates that a large section of the Irish manufacturing industry still has a long way to go in comprehensively adopting a TQM approach in their organisations (Ismail and Hashmi, 1999).…”
Section: Tqm In Practicementioning
confidence: 99%
“…However, Ennis & Harrington (2001) found that only 25% of the hospitals they surveyed had formal TQM programs, and half of those had started in the year prior to the survey.…”
Section: Changing Markets Technologies and Business Strategiesmentioning
confidence: 96%